Right ventricular-pulmonary arterial coupling impairment and exercise capacity in obese adults - Zhou, Na; Forton, Kevin; Motoji, Yoshiki; Scoubeau, Corentin; Klass, Malgorzata; Naeije, Robert; Faoro, Vitalie (Frontiers in Cardiovascular Medicine, 2022)
Background Obesity-related exercise intolerance may be associated with pulmonary vascular and right ventricular dysfunction. This study tested the hypothesis that decreased pulmonary vascular reserve and right ventricular (RV)-pulmonary arterial (PA) uncoupling contributes to exercise limitation in subjects with obesity. Methods Seventeen subjects with obesity were matched to normo-weighted healthy controls. All subjects underwent; exercise echocardiography, lung diffusing capacity (DL) for nitric oxide (NO) and carbon monoxide (CO) and an incremental cardiopulmonary exercise test. Cardiac output (Q), PA pressure (PAP) and tricuspid annular plane systolic excursion (TAPSE) were recorded at increasing exercise intensities. Pulmonary vascular reserve was assessed by multipoint mean PAP (mPAP)/Q relationships with more reserve defined by lesser increase in mPAP at increased Q, and RV-PA coupling was assessed by the TAPSE/systolic PAP (sPAP) ratio. Results At rest, subjects with obesity displayed lower TAPSE/sPAP ratios (1.00 ± 0.26 vs. 1.19 ± 0.22 ml/mmHg, P < 0.05), DLCO and pulmonary capillary blood volume (52 ± 11 vs. 64 ± 13 ml, P < 0.01) compared to controls. Exercise was associated with steeper mPAP-Q slopes, decreased TAPSE/sPAP and lower peak O2 uptake (VO2peak). The changes in TAPSE/sPAP at exercise were correlated to the body fat mass (R = 0.39, P = 0.01) and VO2peak (R = 0.44, P < 0.01). Conclusion Obesity is associated with a decreased pulmonary vascular and RV-PA coupling reserve which may impair exercise capacity.